Penatalaksanaan Fisioterapi Pada Kasus Post Aff Implant Radius Distal Sinistra Di RST Dr.Soedjono Magelang - Lutfiani, Fitri; , Dwi Rosella Komala Sari S.Fis, M.Fis (2016)
Background of the study: Radius fracture is continuity bone dissolution that occurs in the radius bone, which may occur due to fall with your arms open or direct blow when a motor vehicle accident or a fight. Aff implant Radius is the term used in orthopedic surgery to remove the implant (pen) that is currently on the bone Radius. The modalities encompasses used are Infra Red (IR) and exercise therapy. Objectives of the study: to know the benefits of Infrared (IR) and exercise therapy to decrease pain, increase Range of Motion and decrease oedema in post aff implant radius. Results: After conducting some therapies for six times, the results showed that there was a decrease of movement pain, T1: 6 (a light pain) into T6: 4 (mild pain); decrease oedema of T1: 46 cm into T6: 44cm, a vast increase range of motion left wrist joint in the dorsi-flexion and palmar-flexion of T1: S: 300-0-240 becomes T6: S: 400-0-450 Conclusions: Infra Red (IR) and exercise therapy can decrease movement pain, decrease the oedema and increase the Range of Motion in the left hand.